The constitutionality control of the laws in Spain - Carruitero Lecca, Francisco (2008)
The control of the constitutionality of the laws is a mechanism that constitutes a medullar element in the creation of a Constitutional State of the Rights, it actually makes possible the practice of the constitutional supremacy. In order to that, the model applied in Spain is one the best achieved, especially thanks to the presence of the Constitutional Court, that through its jurisprudence established an indisputable line of a system that privileges constitutional norms above all. For this reason, in the present article we will develop the control system of constitutionality of the laws in Spain: from the organs that manage it to the mechanisms that make it possible.